Lecture’s Oral Feedback toward Sophomore College Students’ Speech Errors (RETAIN, 2020)
Lecturers or teachers can find students who made speech errors easily on the students’speaking performance. One of the way to help the students reduced their speech errors is through oral feedback. This study was conducted to find out how does the lecture provided oral feedback to each type of speech errors that the students made. The subject of this study was the lecture which gave oral feedback to the sophomore college students in academic speaking class. The researcher used observation as the data collection technique. The result from this study showed that The lecture used descriptive feedback, evaluative feedback and corrective feedback as the main feedback for the seven types of speech errors. Each type of speech errors that the students made gets their specific oral feedback from the lecture. Each type of feedbacks that the lecture did have their own purpose of helping the students to reduce their speech errors.